2019
DOI: 10.1001/jamadermatol.2018.4944
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Oral Antibiotic Prescription in Dermatology, 2008 to 2016

Abstract: IMPORTANCE Dermatologists prescribe more oral antibiotic courses per clinician than any other specialty, and this use puts patients at risk of antibiotic-resistant infections and antibiotic-associated adverse events. OBJECTIVE To characterize the temporal trends in the diagnoses most commonly associated with oral antibiotic prescription by dermatologists, as well as the duration of this use. DESIGN, SETTING, AND PARTICIPANTS Repeated cross-sectional analysis of antibiotic prescribing by dermatologists from Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 63 publications
1
77
2
3
Order By: Relevance
“…The indication for and duration of systemic antibiotics should be limited, particularly when effective alternatives are available. 22…”
Section: Our Experience and Recommendationsmentioning
confidence: 99%
“…The indication for and duration of systemic antibiotics should be limited, particularly when effective alternatives are available. 22…”
Section: Our Experience and Recommendationsmentioning
confidence: 99%
“…Although overall oral antibiotic use among dermatologists is declining, antibiotic prescribing by dermatologists associated with benign excisions, malignant excisions, and Mohs surgery has been increasing over the past decade and there is substantial geographic variation in antibiotic use. 10 These prolonged courses of postoperative antibiotics may place patients at unnecessary risk of adverse outcomes without providing additional value with respect to prevention of postoperative complications. Given the substantial geographic variation in practice patterns, there are likely opportunities to optimize antibiotic use associated with dermatologic procedures to improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although use of oral antibiotics for chronic inflammatory conditions such as acne and rosacea appears to be decreasing, use of oral antibiotics associated with dermatologic procedures has increased substantially over the past decade. 10 In addition, a 2012 survey 11 sent to American College of Mohs Surgery members found that there may be antibiotic overuse associated with dermatologic procedures. However, factors associated with oral antibiotic use, differences in use between procedure types, and geographic variation in prescribing practices have not been well characterized.…”
mentioning
confidence: 99%
“…Dermatologists are the most common prescribers of oral antibiotics in the United States, and extended courses of antibiotics are commonly prescribed for inflammatory conditions such as acne, rosacea, and hidradenitis suppurativa. 20,21 Oral antibiotics are useful when treating moderate to severe inflammatory acne that is refractory to topical therapy. 12 The tetracycline family of antibiotics is considered the first-line systemic antibiotic treatment for acne.…”
Section: Relevance To Patient Care and Clinical Practicementioning
confidence: 99%